Rd sharma solutions
Our top 5% students will be awarded a special scholarship to Lido.

Algebraic Expressions | Algebraic Expressions Exercise 7.2

Question 17
  1. From the sum of x2 + 3y2 − 6xy, 2x2 − y2 + 8xy, y2 + 8 and x2 − 3xy subtract−3x2 + 4y2– xy + x – y + 3.
Looking to do well in your science exam ?  
Learn from an expert tutor. Book a free class!

First we have to find the sum of (x2 + 3y2- 6xy), (2x2 - y2 + 8xy), (y2 + 8) and (x2- 3xy)

={(x2 + 3y2 - 6xy) + (2x2 - y2+ 8xy) + ( y2 + 8) + (x2 - 3xy)}

={x2 + 3y2 - 6xy + 2x2 - y2+ 8xy + y2 + 8 + x2 - 3xy}

= {x2+ 2x2+ x2 + 3y2-y2 + y2- 6xy + 8xy - 3xy + 8}

= 4x2 + 3y2 - xy + 8

Now, from the result subtract the −3x2 + 4y2 –xy + x – y + 3.

Therefore, required expression = (4x2 + 3y2 -xy + 8) - (- 3x2 + 4y2 - xy + x - y + 3)

= 4x2 + 3y2 - xy + 8 + 3x2- 4y2 + xy - x + y - 3

= 4x2 + 3x2+ 3y2- 4y2- x+ y - 3 + 8

= 7x2 - y2- x + y + 5

Set your child up for success with Lido, book a class today!

Our top 5% students will be awarded a special scholarship to Lido.

subject-cta

Question 17

  1. From the sum of x2 + 3y2 − 6xy, 2x2 − y2 + 8xy, y2 + 8 and x2 − 3xy subtract−3x2 + 4y2– xy + x – y + 3.
Looking to do well in your science exam ? Learn from an expert tutor. Book a free class!

First we have to find the sum of (x2 + 3y2- 6xy), (2x2 - y2 + 8xy), (y2 + 8) and (x2- 3xy)

={(x2 + 3y2 - 6xy) + (2x2 - y2+ 8xy) + ( y2 + 8) + (x2 - 3xy)}

={x2 + 3y2 - 6xy + 2x2 - y2+ 8xy + y2 + 8 + x2 - 3xy}

= {x2+ 2x2+ x2 + 3y2-y2 + y2- 6xy + 8xy - 3xy + 8}

= 4x2 + 3y2 - xy + 8

Now, from the result subtract the −3x2 + 4y2 –xy + x – y + 3.

Therefore, required expression = (4x2 + 3y2 -xy + 8) - (- 3x2 + 4y2 - xy + x - y + 3)

= 4x2 + 3y2 - xy + 8 + 3x2- 4y2 + xy - x + y - 3

= 4x2 + 3x2+ 3y2- 4y2- x+ y - 3 + 8

= 7x2 - y2- x + y + 5

Our top 5% students will be awarded a special scholarship to Lido.

subject-cta
Connect with us on social media!
2021 © Quality Tutorials Pvt Ltd All rights reserved
`